G415(P) Outpatient referral pathway for children with murmurs: Does the current system work?. (24th May 2017) - Lynn, M; Mustafa, K; Davidson, C
Abstract : Over the last few years there has been a substantial increase in Paediatricians with Expertise in Cardiology (PEC) availability in non-specialist cardiology hospitals (68% in 2015 vs 35% in 2008). This has led to debate within individual trusts about outpatient referral pathways – in particular for children referred by general practitioners (GPs) with a murmur. Within our trust most of these children are seen first by a general paediatrician then referred on to PEC if necessary. Our aim was to establish whether this current system operates efficiently by examining outcomes for these patients (in terms of discharge or referral) as well as diagnostic rates of cardiac pathology. All GP referrals received within our trust between January and March 2015 were reviewed. The outcomes of those deemed to be 'cardiology' referrals (i.e. presenting with chest pain, syncope, palpitations, possible cyanotic episodes – or a murmur) were then assessed. In total 772 referrals were received from GPs of which 75 (9.7%) were defined as 'cardiology', with murmur being the most common reason for referral (45.5%) in this group. 58.5% of children with a murmur were seen first by a general paediatrician and of these, 62.5% were then referred to a PEC clinic. On average it took 65.8 days to general paediatrician appointment and 57.4 days to PEC direct but 150.2 total days to PEC if referred on by a general paediatrician. Of all those seen by PEC with a murmur, 83% (24/29) were discharged after echocardiogram with a diagnosis of innocent murmur. The remainder had a patent ductus arteriosus (6.8%), ventricular septal defect (3.4%), mild pulmonary stenosis (3.4%) or abnormalities on electrocardiogram (3.4%). Using the current referral pathway, patients with murmurs required 53 new patient clinic slots and 1 follow up slot over 3 months (in both general and PEC clinics), which could be reduced to 38 if seen solely by a PEC. Nine extra cardiology slots would be required (3/month) which has implications for PEC workload and job planning but 25 new patient general paediatric slots would be freed up within the trust (8.3/month) improving waiting times and patient experience.